Pengembangan Manajemen Sumber Daya Manusia dalam Era Digital di Lembaga Kelas Lancar Mengaji Private - Putri, Nabila; Jamilus, Jamilus (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
The objectives of this study are to: (1) Describe the development of human resource management in the Rankar Menghazi class. (2) Describe the impact of the digital era on the development of human resource management. This research is a qualitative study using data collection techniques in the form of observation and interviews. The results of this study include the planning, implementation and evaluation processes of human resource development management in the Lunker Menghazi class. Training and development under the guidance of Tarshin Training Development. The following steps are taken to carry out personnel training for the Lancar Mengaji class. Identifying needs, setting goals, establishing programs. Management concepts were successfully implemented according to teachers' knowledge. Digitalization has a great impact on educational institutions that manage the personnel development of the Lancar Mengaji Classroom Institute. The teachers can interact and expand their knowledge through the platform